Mobile and web messaging messaging protocols for web and mobile devices - Mesnil, Jeff (O'Reilly Media, 2014)
The use of mobile devices is increasing and widening. Not only are smartphones and tablets connected to the Internet but also automation devices, car systems, and more. With the messaging technology covered in this practical guide, you'll learn how to apply protocols that use the most critical resources (network bandwith and memory usage) efficiently - and guarantee that the data will be effectively delivered even in the event of loss of network connectivity.